Transformations of chloro and nitro groups during the peroxymonosulfate-based oxidation of 4-chloro-2-nitrophenol. (September 2015) - Zhou, Jun; Xiao, Jiuhua; Xiao, Dongxue; Guo, Yaoguang; Fang, Changling; Lou, Xiaoyi; Wang, Zhaohui; Liu, Jianshe
Highlights: Degradation of 4C2NP undergoes denitration, dechlorination and denitrochlorination. A de novo formation of chlorinated compounds was found. Re-nitration may be avoided in SO4 ⋅− -based system, unlike in OH-based systems. Abstract: Dechlorination and denitration are known to occur during the oxidative degradation of chloronitroaromatic compounds, but the possibility of re-chlorination and re-nitration of chloro and nitro groups is not assessed despite of its importance in evaluating the applicability of advanced oxidation processes (AOPs). In this study, transformation of chloro and nitro groups in degradation of 4-chloro-2-nitrophenol (4C2NP) by sulfate radical generated via Co-mediated peroxymonosulfate activation was investigated. Both chloride and nitrate ions were found as the main inorganic products of chloro and nitro groups in 4C2NP, but their levels were much lower than that of degraded parent 4C2NP. A typical dual effect of chloride on the 4C2NP degradation kinetics was observed, whereas no measurable influence was found for addition of low level nitrate. Re-chlorination took place, but re-nitration was not verified because several polychlorophenols but none of polynitrophenols were detected. The specific degradation mechanism involved in the transformation of nitro group and chloro group was proposed.